Utilization of Vigna mungo flour as fat mimetic in biscuits: Its impact on antioxidant profile, polyphenolic content, storage stability, and quality attributes. Issue 4 (6th August 2020) - Saeed, Syed Muhammad Ghufran; Ali, Syed Arsalan; Ali, Rashida; Naz, Shahina; Sayeed, Syed Asad; Mobin, Lubna; Ahmed, Raheel
Abstract: In the present study, an effort was made to incorporate Vigna mungo flour (VMF) as a fat mimetic for the development of functional biscuits. Rheological properties of dough, pasting profile, total phenolic content (TPC) and total flavonoid content (TFC), antioxidant activities (1, 1‐diphenyl‐2‐picrylhydrazyl [DPPH] inhibition and ferric reducing antioxidant power [FRAP]), shelf life, and nutritional and sensory properties of the samples were analyzed. An increase in DPPH inhibition, FRAP, TPC, and TFC was observed with increase in the concentration of VMF in wheat flour (WF). The addition of VMF resulted in increased water absorption (58.71–72.40%) and dough stability time (6.30–13.11 min). Set back viscosities (479–81 torque) decreased significantly ( P ≤ 0.05), whereas break down viscosities (378–447 torque) increased. The baking process decreased the IC50 values of DPPH inhibition (255.40–169.21 mg/ml) and FRAP (114.45–34.12 mg/ml), although TPC and TFC decreased. The study of shelf life for 2 months revealed no significant difference ( P ≤ 0.05) in antioxidant, phenolics, and flavonoids contents of VMF‐WF biscuits. Furthermore, the antioxidants, TFC, and TPC compounds were undetected in control throughout the storage period. The increase in both peroxide value (3.9 mEqO2 /kg of fat) and free fatty acid (0.87%) was significantly lower ( P ≤ 0.05) than that of the control biscuits during storage but were in an acceptable range. It correlates to the enhanced activity of natural antioxidants as TPC and TFC in VMF‐WF biscuits, which are responsible for the decrease in the rate of oxidation. Nutritional data of VMF‐WF biscuits revealed that protein (11.20–15.85%), crude fiber (0.21–2.01%), and ash content (0.53–4.01%) significantly increased ( P ≤ 0.05) and calories (497–430 kcal/100 g) reduced because of the addition of fat mimetic. Biscuits prepared with VMF 15% demonstrated superior quality as compared with control. In conclusion, it could be suggested that the addition of VMF as a fat mimetic in biscuits may increase antioxidant and polyphenolic contents with enhanced storage stability. The reduced calories, increased protein, fiber, mineral contents, and enhanced antioxidant activity considerably increase the nutritional status of the biscuits.